Benarkah Guru Mengalami Kelelahan Emosional? (Studi Dampak Penerapan Lima Hari Sekolah) - Muhammad Reza Aldian; Achmad Sudjadi; Dwita Darmawati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
This research is a survey of state junior high school teachers in the city of Purwokerto. The aim is to find out whether there is emotional exhaustion of teachers due to the application of the 5-day school policy, as well as its impact on job satisfaction and affective commitment. Data were obtained from 94 respondents who were determined using the purposive sampling method. Analysis using descriptive statistics shows that (1) there was no emotional exhaustion on the teacher due to the application of 5 school days. In addition, the regression analysis shows that (2) emotional fatigue does not negatively affect affective commitment, (3) emotional fatigue does not have a negative effect on job satisfaction, (4) job satisfaction has a positive effect on affective commitment, and (5) job satisfaction does not mediate the relationship between emotional exhaustion and affective commitment. Some implications are given based on the results of the study